КОМПОНЕНТНА СТРУКТУРА МОРАЛЬНО-ЕСТЕТИЧНОЇ АКТИВНОСТІ ВЧИТЕЛЯ-МУЗИКАНТА (Педагогіка вищої та середньої школи, 2006)
In the article, the structure, the topical ness, and the criterions of the formed moral-aesthetic activity of teacher-musician are considered.